Cholesterol-modified prognostic nutritional index as an independent prognostic biomarker in primary biliary cholangitis patients - Zhu, Huiling; Zheng, Mengyao; Li, Wenbin; Huang, Yaqin; Zhang, Lili; Yang, Wenting; Yang, Jinhui (BMC gastroenterology, 2025)
Primary biliary cholangitis (PBC) is a chronic cholestatic liver disease characterized by inflammation of the interlobular bile ducts, often associated with malabsorption of fat-soluble vitamins and osteoporosis. Thus, evaluating the nutritional status of patients with PBC and implementing appropriate interventions are significant. But CPNI in determining the nutritional status and forecasting survival outcome among patients with PBC remains unclear. A total of 262 patients with PBC were retrospectively enrolled at the Second Affiliated Hospital of Kunming Medical University between January 2013 and November 2023. We used the receiver operating characteristic (ROC) curve, Kaplan-Meier survival curve, and logistic regression analysis to evaluate the predictive effects of several nutritional assessments. These assessments included the controlling nutritional status (CONUT), geriatric nutritional risk index (GNRI), prognostic nutritional index (PNI), and Cholesterol-modified Prognostic Nutritional Index (CPNI), which were evaluated for their predictive effect on the prognosis of PBC patients. In our study, after adjusting for various confounding factors, multivariate cox regression analyses revealed that CPNI (HR: 1.114, 95% CI: 1.003-1.237, P = 0.044), age (HR: 1.071, 95% CI: 1.018-1.127, P < 0.009), total bilirubin (HR:1.019, 95% CI:1.009-1.09, P < 0.001) were independent risk factors for death in patients with PBC. The Kaplan-Meier curves and ROC curves used to assess predictive accuracy showed that CPNI(0.788) had superior prognostic performance for OS compared to other nutritional indices, such as CONUT(0.724), GNRI(0.755), PNI(0.776), and UK-PBC(0.660)(P < 0.05). CPNI is superior to other nutritional scores in the prognostic assessment of PBC patients.